Use of resin composition as gel coating and leading edge protective agent for wind turbine blade

By using a composition of urethane resin and epoxy (meth)acrylate resin as the leading edge protection material of wind power blades, the problem of insufficient construction time-consuming, labor-intensive and corrosion-resistant is solved, and efficient air is achieved Power characteristics are maintained and power generation efficiency is improved.

CN119220167APending Publication Date: 2024-12-31RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410824394.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The leading edge protection materials of existing wind power blades consume time and effort during construction, and can easily lead to a reduction in aerodynamic characteristics, insufficient corrosion resistance, and affect power generation efficiency.

Method used

The urethane resin composition containing the urethane structure and carbonate structure is used as the gel coating and leading edge protector, by combining the urethane resin and epoxy (meth)acrylate in the same molecule Resin forms a film with high mechanical strength and corrosion resistance, and is used for leading edge protection of wind power blades.

Benefits of technology

It reduces the labor and time of construction, avoids the reduction of aerodynamic characteristics, and significantly improves the corrosion resistance of wind power blades, ensuring the stability of power generation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220167A_ABST
    Figure CN119220167A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing the use of a resin composition as a leading edge protective agent for various types of wind turbine blades, said resin composition being capable of forming a leading edge protective material that takes little effort and time in construction, can avoid a decrease in aerodynamic characteristics, and has excellent corrosion resistance. The solution is the use of a resin composition containing a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coating and leading edge protective agent for a wind turbine blade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the use of a resin composition as a gel coating and leading edge protective agent for a wind power generation blade. Background Art

[0002] With the goal of maximizing power generation efficiency, wind turbine blades are becoming larger. As wind turbine blades become larger, damage or wear (erosion) of the leading edge of wind turbine blades due to rain or sand becomes a problem. Erosion reduces the aerodynamic properties of wind turbine blades, resulting in reduced power generation efficiency. Leading edge protection (LEP) is installed on wind turbine blades for the purpose of preventing erosion. So far, different types of LEPs have been developed, such as sheet type, coating type, and mold type.

[0003] Patent document 1 (US Patent Application Publication No. 2020 / 0040869) describes a method for applying a protective layer to the outer surface of a wind turbine rotor blade. The method includes the following steps: a step of preparing a protective layer to be applied to the outer surface of a rotor blade; a step of providing an air outlet passage between the rotor blade and the protective layer; a step of attaching the protective layer to the outer surface of the rotor blade; and a step of extracting air through the air outlet passage.

[0004] Patent document 2 (International Publication No. 2012 / 102294) describes a blade body, characterized in that a laminated protective sheet is bonded to at least a portion of at least the leading edge of a blade body main body made of fiber reinforced plastic (FRP), and the laminated protective sheet has an adhesive layer, an intermediate base fabric layer and a surface durable layer in sequence from the blade body main body side.

[0005] Patent document 3 (US Patent Application Publication No. 2021 / 0130647) describes a coating material composition used for the manufacture of an erosion-stable coating used as erosion protection, in particular, edge protection of a rotor blade. The composition comprises a stock component and a curing agent component, the stock component comprising at least one trifunctional polycaprolactone polyol, at least one polycarbonate diol, or at least one trifunctional polycaprolactone polyol and polycarbonate diol, and the curing agent component comprises at least one crystallization-resistant isocyanate functional prepolymer.

[0006] Patent document 4 (International Publication No. 2016 / 075619) describes a method for producing a protective cover for a wind turbine blade, characterized in that a) a polyol and butanediol are mixed, b) the mixture obtained from a) is tempered and degassed, c) isocyanate is tempered and degassed, d) the degassed mixture obtained from b) and the degassed isocyanate obtained from c) are pumped into a mold through a mixing head, e) the mixture is cured in the mold, and f) the cured article is taken out of the mold.

[0007] Non-patent document 1 (Wind Energy Utilization Science, 2021, Vol. 43, p. 210) states that when an erosion protection sheet is constructed on a wind turbine blade, the aerodynamic characteristics of the wind turbine blade are reduced due to the height difference generated at the boundary between the wind turbine blade and the protection sheet.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: U.S. Patent Application Publication No. 2020 / 0040869

[0011] Patent Document 2: International Publication No. 2012 / 102294

[0012] Patent Document 3: U.S. Patent Application Publication No. 2021 / 0130647

[0013] Patent Document 4: International Publication No. 2016 / 075619

[0014] Non-patent literature

[0015] Non-patent document 1: Hirokazu Kawabata, "Evaluation of aerodynamic performance of engineering protection and construction equipment", Wind Power Equipment Utilization Equipment, 2021, Vol. 43, p. 210 Summary of the invention

[0016] Problems to be solved by the invention

[0017] The protective layer described in Patent Document 1 is a sheet that is applied in a post-process after the blade is manufactured, and the construction takes a lot of effort and time. In addition, if the protective layer is applied in a post-process, the aerodynamic characteristics of the blade may be reduced due to the height difference generated at the boundary between the protective layer and the blade, as described in Non-Patent Document 1. Since the laminated protective sheet described in Patent Document 2 is attached to the blade through an adhesive layer, the laminated protective sheet may be peeled off from the blade during long-term use, reducing the aerodynamic characteristics or generating noise. When the thickness of the protective layer or the laminated protective sheet is, for example, 300 μm or more in order to ensure long-term corrosion resistance, the aerodynamic characteristics of the blade are greatly reduced.

[0018] The coating material composition described in Patent Document 3 is excellent in workability, but has low curability and therefore it is difficult to obtain a sufficient level of corrosion resistance.

[0019] The method described in Patent Document 4 requires the protective cover to be preformed according to the shape of the blade, which limits the blades to which it can be applied. The thickness of the protective cover as a molded product also tends to increase, which tends to reduce the aerodynamic characteristics of the blade.

[0020] Furthermore, when a sheet, coating or molded product is applied to a blade, it may be necessary to peel off or remove a coating such as a gel coating on the surface of the blade in order to improve bonding properties.

[0021] The present disclosure provides a resin composition capable of forming LEP having excellent erosion resistance and requiring little labor and time for construction, while avoiding deterioration in aerodynamic properties, as a leading edge protective agent for various types of wind turbine blades.

[0022] Means for solving problems

[0023] The present inventors have discovered that by using a resin composition comprising a carbamate resin having a carbamate structure and a carbonate structure in the same molecule as a gel coat and leading edge protective agent when manufacturing wind turbine blades, LEP which can reduce the labor and time required for construction, avoid a decrease in aerodynamic characteristics, and has excellent erosion resistance can be applied to various types of wind turbine blades, thereby completing the present invention.

[0024] The present disclosure includes the following aspects.

[0025] [Solution 1]

[0026] A resin composition comprising a urethane resin having a urethane structure and a carbonate structure in the same molecule is used as a gel coat and leading edge protective agent for a wind turbine blade.

[0027] [Solution 2]

[0028] According to the use described in Embodiment 1, the urethane resin is a urethane (meth)acrylate resin.

[0029] [Solution 3]

[0030] According to the use of embodiment 1 or 2, the resin composition further comprises an epoxy (meth)acrylate resin.

[0031] [Solution 4]

[0032] According to the use according to any one of aspects 1 to 3, the resin composition contains 10% by mass to 90% by mass of the urethane resin.

[0033] [Solution 5]

[0034] The use according to any one of embodiments 1 to 4, wherein the urethane resin is a reaction product of a composition comprising a polycarbonate polyol and a polyisocyanate, and the molar ratio (OH [mol] / NCO [mol]) of the hydroxyl group of the polycarbonate polyol to the isocyanate group of the polyisocyanate is 0.5 to 0.9.

[0035] [Solution 6]

[0036] According to the use of embodiment 5, the number average molecular weight of the polycarbonate polyol is 500 to 10,000.

[0037] [Solution 7]

[0038] According to the use of embodiment 5 or 6, the polyisocyanate contains an alicyclic polyisocyanate.

[0039] [Scheme 8]

[0040] According to any one of the first to seventh aspects, the urethane resin has a number average molecular weight of 500 to 30,000.

[0041] [Solution 9]

[0042] According to the use described in any one of the first to eighth aspects, the wind turbine blade has a blade length of 10 m or more.

[0043] Effects of the Invention

[0044] According to the present disclosure, it is possible to form an LEP having excellent erosion resistance, which requires less labor and time for construction and can avoid a decrease in aerodynamic characteristics, on various types of wind turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a schematic cross-sectional view of a wind turbine blade according to one embodiment.

[0046] Figure 2 It is an explanatory diagram of a method for manufacturing a wind turbine blade using one embodiment of a vacuum-assisted impregnation construction method. DETAILED DESCRIPTION

[0047] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. The present disclosure is not limited to the following embodiments, and can be implemented with various modifications within the scope of the spirit of the invention.

[0048] In the present disclosure, when a numerical value is expressed in a range, the numerical values ​​at both ends are the upper limit and the lower limit, respectively, and are included in the range.

[0049] In the present disclosure, “(meth)acryloyl” refers to acryloyl or methacryloyl, “(meth)acrylate” refers to acrylate or methacrylate, and “(meth)acryloyloxy” refers to acryloyloxy or methacryloyloxy.

[0050] In the present disclosure, the term “ethylenically unsaturated bond” refers to a double bond formed between carbon atoms other than carbon atoms forming an aromatic ring, and the term “ethylenically unsaturated monomer” refers to a monomer having an ethylenically unsaturated bond.

[0051] In the present disclosure, the “weight average molecular weight” and the “number average molecular weight” are values ​​determined by measuring at room temperature (23° C.) using gel permeation chromatography (GPC) under the following conditions using a standard polystyrene calibration curve.

[0052] Device: Shodex (trademark) GPC-101 (Raykin Co., Ltd.)

[0053] Column: Shodex (trademark) LF-804 (Raykin Co., Ltd.)

[0054] Column temperature: 40°C

[0055] Sample: 0.2 mass% tetrahydrofuran solution of the sample

[0056] Flow rate: 1mL / min

[0057] Eluent: Tetrahydrofuran

[0058] Detector: Shodex (trademark) RI-71S (Rezonak Co., Ltd.)

[0059] [Use as gel coating and leading edge protection agent for wind turbine blades]

[0060] In one embodiment, there is provided use of a resin composition comprising a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coat and leading edge protective agent for a wind turbine blade.

[0061] By using the resin composition, a film that can be used as a leading edge protection material can be formed and arranged in the manufacture of wind turbine blades, so the process can be shortened and the film can be applied to wind turbine blades of various shapes. In addition, in the heating process for curing the matrix resin, since the film can also be heated and cured, a film with high mechanical strength and bonding force can be applied to the wind turbine blade. Furthermore, since the film is formed along the shape of the mold surface, it does not affect the aerodynamic characteristics of the wind turbine blade, and the reduction of power generation efficiency can be prevented.

[0062] Figure 1 FIG. 1 is a schematic cross-sectional view of a wind turbine blade according to an embodiment of the present invention. Figure 1 , the wind turbine blade 10 is shown as a component, including a fiber-containing substrate 14 and a film 12 disposed on a portion of the leading edge side of the fiber-containing substrate 14. The surface of the film 12 and the surface of the fiber-containing substrate 14 are continuous along the surface of the mold used when manufacturing the wind turbine blade 10, and there is no height difference at the boundary between the film 12 and the fiber-containing substrate 14.

[0063] [Resin composition]

[0064] The resin composition of one embodiment includes a carbamate resin having a carbamate structure and a carbonate structure in the same molecule. The carbamate resin having a carbamate structure and a carbonate structure in the same molecule has both high mechanical strength and excellent elongation characteristics. Therefore, a film having excellent corrosion resistance can be formed as a leading edge protection material.

[0065] 〈Urethane resin〉

[0066] The urethane resin having a urethane structure and a carbonate structure in the same molecule can be obtained by subjecting at least a polyisocyanate to a polyol through an addition polymerization reaction, wherein at least one of the polyisocyanate and the polyol has a carbonate structure. The urethane resin can be used alone or in combination of two or more.

[0067] Examples of polyisocyanates include aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-biphenyl diisocyanate, polymethylene polyphenyl diisocyanate, xylylene diisocyanate, phenylene diisocyanate, and triphenylmethane triisocyanate; alicyclic polyisocyanates such as 4,4'-methylenebiscyclohexyl diisocyanate, isophorone diisocyanate, and cyclohexane-1,3-diylbis(methylene) diisocyanate; and aliphatic polyisocyanates such as 1,6-hexamethylene diisocyanate and trimethylhexamethylene diisocyanate; and adducts, isocyanurates, and biuret forms of these polyisocyanates. The polyisocyanates may be used alone or in combination of two or more.

[0068] From the viewpoint of the mechanical strength and weather resistance of the film, the polyisocyanate preferably contains an alicyclic polyisocyanate, and more preferably contains at least one selected from 4,4′-methylenebiscyclohexyl diisocyanate and isophorone diisocyanate.

[0069] As the polyol, a polycarbonate polyol that can introduce a carbonate structure into a urethane resin is generally used. The polycarbonate polyol can be synthesized using an alkanediol and a carbonic acid diester as raw materials under an ester exchange catalyst. As the alkanediol, for example, 1,6-hexanediol, 1,5-pentanediol, 1,4-butanediol, and 2-methyl-1,3-propanediol can be cited. The polycarbonate polyol can form a film having excellent mechanical strength and elongation properties. The polyol can be used alone or in combination of two or more.

[0070] From the viewpoint of the mechanical strength and elongation characteristics of the film, the number average molecular weight (Mn) of the polycarbonate polyol is preferably 500 or more, more preferably 600 or more, further preferably 700 or more, preferably 10,000 or less, more preferably 8,000 or less, and further preferably 5,000 or less. The combination of these lower limits and upper limits may be any combination. The number average molecular weight of the polycarbonate polyol is preferably 500 to 10,000, more preferably 600 to 8,000, and further preferably 700 to 5,000. If Mn is 500 or more, a film having excellent mechanical strength can be formed. If Mn is 10,000 or less, a film having excellent elongation characteristics can be formed.

[0071] The polyol may include a low molecular weight polyol as a chain extender. The low molecular weight polyol can increase the molecular weight of the urethane resin and further improve the mechanical strength of the film. As the low molecular weight polyol, for example, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, 1,1-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, xylylene dimethanol, bis(p-hydroxy)diphenyl, bis(p-hydroxyphenyl)propane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxyethoxy)phenyl]sulfone, and 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane. The low molecular weight polyol may be used alone or in combination of two or more.

[0072] The amount of polyisocyanate used can be designed based on the molar ratio (OH [mol] / NCO [mol]) of the hydroxyl group of the polyol and the isocyanate group of the polyisocyanate. The molar ratio is preferably 0.5 or more. The molar ratio is preferably 0.9 or less, more preferably 0.8 or less, and further preferably 0.7 or less. The combination of these lower limits and upper limits can be any combination. The molar ratio is preferably 0.5 to 0.9, more preferably 0.5 to 0.8, and further preferably 0.5 to 0.7. If the molar ratio is 0.9 or less, the mechanical strength of the film can be improved. If the molar ratio is 0.5 or more, the elongation characteristics of the film can be improved.

[0073] In an embodiment in which the urethane resin is a reaction product of a composition comprising a polycarbonate polyol and a polyisocyanate, the molar ratio of the hydroxyl group of the polycarbonate polyol to the isocyanate group of the polyisocyanate (OH [mol] / NCO [mol]) is preferably 0.5 or more. The molar ratio is preferably 0.9 or less, more preferably 0.8 or less, and further preferably 0.7 or less. The combination of these lower limits and upper limits may be any combination. The molar ratio is preferably 0.5 to 0.9, more preferably 0.5 to 0.8, and further preferably 0.5 to 0.7.

[0074] The reaction temperature of the addition polymerization reaction is not particularly limited, but is preferably 20°C to 200°C, more preferably 50°C to 150°C, and further preferably 80°C to 120°C.

[0075] The addition polymerization reaction can be carried out using a catalyst. Examples of the catalyst include amine compounds such as triethylamine, N-ethylmorpholine, triethylenediamine, and diazabicycloundecene; organic tin compounds such as trimethyltin laurate and dibutyltin dilaurate; organic titanium compounds; and organic lead compounds such as lead 2-ethylhexanoate. The catalyst may be used alone or in combination of two or more.

[0076] The addition polymerization reaction can be carried out in the substantial absence of a solvent or in the presence of a solvent. Examples of the solvent include dimethylformamide, diethylformamide, dimethylacetamide, dimethyl sulfoxide, tetrahydrofuran, methyl isobutyl ketone, dimethicone, and the like. The solvent may be used alone or in combination of two or more.

[0077] The carbamate resin is preferably a carbamate (meth) acrylate resin. The carbamate (meth) acrylate resin can be cured by heating to form a film with high mechanical strength. As the carbamate (meth) acrylate resin, for example, a resin obtained by introducing a (meth) acryloyl group into a terminal hydroxyl group or an isocyanate group of a carbamate resin obtained by reacting the above-mentioned polyisocyanate with the above-mentioned polyol can be used. The carbamate (meth) acrylate resin can be used alone or in combination of two or more.

[0078] In the synthesis of the urethane (meth)acrylate resin, when introducing a (meth)acryloyl group, for example, a method of reacting a hydroxyl group-containing (meth)acrylic compound with a terminal isocyanate group or a method of reacting an isocyanate group-containing (meth)acrylic compound with a terminal hydroxyl group can be used. The hydroxyl group-containing (meth)acrylic compound and the isocyanate group-containing (meth)acrylic compound can be used alone or in combination of two or more.

[0079] Examples of the hydroxyl group-containing (meth)acrylic acid compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified hydroxyalkyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, tri(hydroxyethyl)isocyanuric acid di(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol mono(meth)acrylate, and hydroxyethyl acrylamide, and 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, caprolactone-modified hydroxyalkyl (meth)acrylate, and hydroxyethyl acrylamide are preferred.

[0080] As a (meth)acrylic compound containing an isocyanate group, 2-(meth)acryloyloxyethyl isocyanate, 2-(meth)acryloyloxypropyl isocyanate, and 1,1-bis(acryloyloxymethyl)ethyl isocyanate are mentioned, for example.

[0081] After the synthesis of the urethane (meth)acrylate resin, the unreacted hydroxyl group-containing (meth)acrylic compound or the unreacted isocyanate group-containing (meth)acrylic compound can be used as an ethylenically unsaturated monomer described below.

[0082] The number average molecular weight (Mn) of the urethane resin is preferably 500 or more, more preferably 700 or more, further preferably 1,000 or more, preferably 30,000 or less, more preferably 25,000 or less, and further preferably 20,000 or less. The combination of these lower limits and upper limits may be any combination. The number average molecular weight of the urethane resin is preferably 500 to 30,000, more preferably 700 to 25,000, and further preferably 1,000 to 20,000. If the number average molecular weight of the urethane resin is 500 to 30,000, the mechanical strength and corrosion resistance of the film become better.

[0083] The resin composition contains preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more of a carbamate resin. The resin composition contains preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less of a carbamate resin. The combination of these lower limits and upper limits can be any combination. The resin composition contains preferably 10% to 90% by mass, more preferably 20% to 80% by mass, and further preferably 30% to 70% by mass of a carbamate resin. If the content of the carbamate resin is 10% by mass or more, the erosion resistance of the film becomes better. If the content of the carbamate resin is 90% by mass or less, the coating property of the resin composition is good. In the present disclosure, the content of the carbamate resin is converted to solid content.

[0084] 〈Epoxy (meth)acrylate resin〉

[0085] The resin composition of one embodiment further includes an epoxy (meth) acrylate resin. The epoxy (meth) acrylate resin is generally a compound having an ethylenically unsaturated bond obtained by a ring-opening reaction between an epoxy group of an epoxy compound having two or more epoxy groups and a carboxyl group of an unsaturated monobasic acid having an ethylenically unsaturated bond and a carboxyl group. The epoxy (meth) acrylate resin may be used alone or in combination of two or more.

[0086] The epoxy compound is not particularly limited as long as it is a compound having two or more epoxy groups. As the epoxy compound, for example, at least one selected from bisphenol epoxy compounds, hydrogenated bisphenol epoxy compounds, and novolac phenol epoxy compounds can be used. These epoxy compounds can further improve the mechanical strength and corrosion resistance of the film.

[0087] Examples of the bisphenol-type epoxy compound include substances obtained by reacting bisphenol compounds such as bisphenol A, bisphenol F, bisphenol S and tetrabromobisphenol A with epichlorohydrin or methyl epichlorohydrin; and substances obtained by reacting a glycidyl ether of any one or more of the above bisphenol compounds, and a condensate of any one or more of the above bisphenol compounds, with epichlorohydrin or methyl epichlorohydrin.

[0088] Examples of the hydrogenated bisphenol-type epoxy compound include those obtained by reacting hydrogenated bisphenol with epichlorohydrin or methylepichlorohydrin, and those obtained by reacting glycidyl ether of hydrogenated bisphenol A with a bisphenol compound such as bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A.

[0089] Examples of the novolac phenol-type epoxy compound include compounds obtained by reacting phenol novolac or cresol novolac with epichlorohydrin or methyl epichlorohydrin.

[0090] From the viewpoint of the mechanical strength of the film, the epoxy compound is preferably at least one selected from a bisphenol A epoxy resin and a hydrogenated bisphenol A epoxy resin.

[0091] As unsaturated monocarboxylic acid, as long as it is a monocarboxylic acid with an ethylenically unsaturated bond, there is no particular limitation. As unsaturated monocarboxylic acid, for example, (meth) acrylic acid, crotonic acid, and cinnamic acid can be cited. From the viewpoint of the mechanical strength and corrosion resistance of the film, the unsaturated monocarboxylic acid is more preferably (meth) acrylic acid, and from the viewpoint of the mechanical strength of the film, it is more preferably methacrylic acid.

[0092] The amount of the unsaturated monobasic acid used is preferably 0.3 to 1.5 mol, more preferably 0.4 to 1.2 mol, and particularly preferably 0.5 to 1.0 mol relative to 1 mol of the total amount of epoxy groups of the epoxy compound. If the amount of the unsaturated monobasic acid used is within the above range, a film having high hardness can be obtained.

[0093] The epoxy (meth)acrylate resin can be synthesized by a known synthesis method, for example, a method in which an epoxy compound and an unsaturated monobasic acid are dissolved in a solvent as required in the presence of an esterification catalyst and reacted at 70 to 150°C, preferably 80 to 140°C, and more preferably 90 to 130°C.

[0094] Examples of the esterification catalyst include tertiary amines such as triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, 2,4,6-tris(dimethylaminomethyl)phenol, and diazabicyclooctane; triphenylphosphine, benzyltriphenylphosphine chloride; The esterification catalyst may be used alone or in combination of two or more.

[0095] The unreacted unsaturated monobasic acid after the synthesis of the epoxy (meth)acrylate resin can be used as an ethylenically unsaturated monomer described below.

[0096] The number average molecular weight (Mn) of the epoxy (meth)acrylate resin is not particularly limited, but is preferably 500 to 30,000, more preferably 700 to 25,000, and further preferably 1,000 to 20,000. When the number average molecular weight of the epoxy (meth)acrylate resin is 500 to 30,000, the mechanical strength and corrosion resistance of the film are further improved.

[0097] In one embodiment, the resin composition comprises 1% to 80% by mass, preferably 3% to 70% by mass, and more preferably 5% to 60% by mass of epoxy (meth) acrylate resin. If the content of epoxy (meth) acrylate resin is 1% by mass or more, the mechanical strength of the film can be improved. If the content of epoxy (meth) acrylate resin is 80% by mass or less, the elongation characteristics of the film can be improved. In the present disclosure, the content of epoxy (meth) acrylate resin is solid content conversion.

[0098] 〈Diluting Monomer〉

[0099] The resin composition may contain an ethylenically unsaturated monomer as a diluent monomer. The diluent monomer can adjust the viscosity of the resin composition and improve workability and coating properties. The diluent monomer may be used alone or in combination of two or more.

[0100] Examples of the ethylenically unsaturated monomer include vinyl compounds such as styrene, vinyltoluene, tert-butylstyrene, methoxystyrene, divinylbenzene, vinylnaphthalene, and acenaphthylene; diene compounds such as butadiene, 2,3-dimethylbutadiene, isoprene, and chloroprene; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, furfuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and the like. (Meth)acrylate compounds such as acrylate, allyl (meth)acrylate, isobornyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecanol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate; (meth)acrylamide compounds such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, and N,N-diisopropyl (meth)acrylamide; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, and sorbic acid; unsaturated dicarboxylic acids such as fumaric acid and maleic acid; unsaturated dicarboxylic acid diesters such as diethyl citraconic acid; monomaleimide compounds such as N-phenylmaleimide; N-(meth)acryloylphthalimide; cinnamic acid; and dihydroxycinnamic acid.

[0101] From the viewpoint of the curing speed and the mechanical strength of the film, the ethylenically unsaturated monomer is preferably at least one selected from styrene, vinyltoluene, methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, tert-butyl(meth)acrylate, phenyl(meth)acrylate, isobornyl(meth)acrylate, and benzyl(meth)acrylate, and more preferably at least one selected from styrene, vinyltoluene, tert-butylmethacrylate, and isobornylacrylate.

[0102] The content of the ethylenically unsaturated monomer is preferably 10% to 95% by mass, more preferably 30% to 90% by mass, and further preferably 50 to 80% by mass relative to the total of the urethane resin, the epoxy (meth)acrylate resin, and the ethylenically unsaturated monomer. If the content of the ethylenically unsaturated monomer is within the above range, the mechanical strength of the film can be further improved.

[0103] 〈Curing agent〉

[0104] In order to promote curing, the resin composition may contain a radical polymerization initiator as a curing agent. If a radical polymerization initiator is added to the resin composition, curing of the resin composition begins. Therefore, for example, in the case of storing the resin composition, it is desirable to add the radical polymerization initiator to the resin composition just before curing the resin composition. In the case of storing the resin composition under conditions where the radical polymerization reaction does not start, from the viewpoint of operating efficiency, the curing agent may also be included in the resin composition in advance. The curing agent may be used alone or in combination of two or more.

[0105] The radical polymerization initiator can be appropriately selected according to the application, curing conditions, etc., and is not particularly limited. Examples of the radical polymerization initiator include thermal radical initiators and photoradical initiators, and thermal radical initiators are preferred from the viewpoint of workability.

[0106] Examples of the thermal radical initiator include diacyl peroxides such as benzoyl peroxide; peroxyesters such as tert-butyl peroxybenzoate; hydroperoxides such as cumene hydroperoxide; dialkyl peroxides such as dicumyl peroxide; ketone peroxides such as methyl ethyl ketone peroxide and acetylacetone peroxide; peroxyketals such as 1,1-dialkyl peroxycyclohexane; alkyl peresters such as alkyl peroxydecanoate; and organic peroxides such as percarbonates such as peroxydicarbonate.

[0107] The amount of the radical polymerization initiator used is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and further preferably 0.5 to 5 parts by mass relative to 100 parts by mass of the total of the urethane resin, the epoxy (meth) acrylate resin, and the ethylenically unsaturated monomer. If the content of the radical polymerization initiator is 0.1 parts by mass or more, the curing of the resin composition can be rapidly performed. If the content of the radical polymerization initiator is 10 parts by mass or less, the balance between productivity and cost is good.

[0108] 〈Curing accelerator〉

[0109] The resin composition may contain a curing accelerator in order to promote the radical polymerization reaction of the resin composition. The curing accelerator may be used alone or in combination of two or more.

[0110] As a curing accelerator, for example, a salt of a metal element and an organic acid can be mentioned. As a metal element, for example, cobalt, vanadium, and manganese can be mentioned. As a specific example of a curing accelerator, 2-ethylhexanoic acid manganese, 2-ethylhexanoic acid cobalt, 2-ethylhexanoic acid zinc, 2-ethylhexanoic acid vanadium, cobalt naphthenate, copper naphthenate, barium naphthenate, acetoacetic acid vanadium, cobalt acetoacetate, and ferric acetoacetate can be mentioned. As a curing accelerator, preferably manganese 2-ethylhexanoate, cobalt 2-ethylhexanoate, and cobalt naphthenate.

[0111] The amount of the curing accelerator used is preferably 0.01 to 6.0 parts by mass, more preferably 0.02 to 4.0 parts by mass, and further preferably 0.03 to 3.0 parts by mass relative to 100 parts by mass of the total of the urethane resin, the epoxy (meth) acrylate resin, and the ethylenically unsaturated monomer. By making the amount of the curing accelerator used in the above range, the free radical polymerization reaction of the resin composition can be rapidly carried out at low temperature to room temperature, for example, in the temperature range of 5°C to 40°C.

[0112] 〈Solvent〉

[0113] The resin composition may contain a solvent. The solvent may be derived from the solvent used when synthesizing the urethane resin or the epoxy (meth) acrylate resin. Examples of the solvent include esters such as n-butyl acetate and n-propyl acetate; and aromatic hydrocarbons such as benzene, toluene, and xylene. In the present disclosure, the above-mentioned diluting monomer is not included in the solvent. The content of the solvent may be appropriately determined according to the application and the coating method. For example, the content of the solvent may be set in such a way that the solid content of the resin composition is 10% to 90% by mass, 20% to 80% by mass, or 30% to 70% by mass.

[0114] <additive>

[0115] The resin composition may further contain additives. Examples of the additives include dispersants, fillers, thixotropic agents, thixotropic properties-imparting aids, colorants, and polymerization inhibitors.

[0116] As a dispersant, DISPERBYK-2152 (made by BYK Japan Corporation) is mentioned, for example.

[0117] As the filler, for example, calcium carbonate, aluminum hydroxide, fly ash, barium sulfate, talc, clay, glass flakes, glass powder, and wood powder can be cited. As the filler, hollow fillers such as glass microspheres, saran resin microspheres, acrylonitrile microspheres, and volcanic ash balls can also be used.

[0118] As thixotropic agent, for example, inorganic powders such as silicon dioxide and clay can be enumerated. Thixotropic agent can adjust the rheological properties of resin combination and improve coating property. In the case where the resin combination includes particles of filler, pigment, etc., thixotropic agent can also suppress the sedimentation of these particles and improve the storage stability of the resin combination.

[0119] Examples of the thixotropy-imparting auxiliary agent include polyethylene glycol, glycerin, polyhydroxycarboxylic acid amide, organic quaternary ammonium salt, and BYK-R-605 (manufactured by BYK Japan Corporation).

[0120] Examples of the colorant include organic pigments, inorganic pigments such as titanium oxide, and dyes.

[0121] Examples of the polymerization inhibitor include hydroquinone, trimethylhydroquinone, p-benzoquinone, naphthoquinone, tert-butylhydroquinone, catechol, p-tert-butylcatechol, and 2,6-di-tert-butyl-4-methylphenol.

[0122] Examples of other additives include a defoaming agent, an ultraviolet absorber, a light stabilizer, a thickener, and a plasticizer.

[0123] 〈Viscosity〉

[0124] The viscosity of the resin composition is preferably 10 mPa·s to 20,000 mPa·s, more preferably 50 mPa·s to 15,000 mPa·s, and further preferably 100 mPa·s to 10,000 mPa·s. By making the viscosity of the resin composition within the above range, workability and coating properties can be improved. In the present disclosure, the viscosity of the resin composition is defined as the shear viscosity at 25° C. and a rotation speed of 100 rpm using a cone / plate viscometer in accordance with JIS K 5600-2-3:2014.

[0125] Below, refer to Figure 2 Each step of the method for manufacturing a wind turbine blade will be described.

[0126] 〈Coating process〉

[0127] In the coating step, the resin composition is applied to at least a portion of the surface of the mold to form a coating film.

[0128] exist Figure 2 (a) shows a cross-sectional view of the mold 20. The mold 20 has a mold surface 22 and is provided with a heater 24 inside for heating the stacked body in the heating step. Figure 2 The mold 20 is shown as a material for forming a part of a wind turbine blade. Figure 2 As shown in (b) of FIG. 1 , the film 12 is formed by applying the resin composition to a portion of the mold surface 22. The film 12 is formed on a portion of the mold surface 22 corresponding to the leading edge of the wind turbine blade.

[0129] The resin composition can be applied to the mold surface using a known coating means such as a sprayer, a brush, a roller, a trowel, a spatula, a syringe, or the like.

[0130] The film formed by coating can be pre-cured at 5° C. to 40° C. for 10 minutes to 72 hours, for example.

[0131] The thickness of the film can be various depending on the shape of the wind turbine blade, the required mechanical strength, etc. In one embodiment, the thickness of the film in the wind turbine blade is 0.5 mm or more. In one embodiment, the thickness of the film is 2 mm or less. The combination of these lower limit values ​​and upper limit values ​​can be any combination. In one embodiment, the thickness of the film is 0.5 mm to 2 mm. By making the thickness of the film 0.5 mm or more and 2 mm or less, a film with high mechanical strength can be applied to the wind turbine blade.

[0132] In one embodiment, a film is formed on a portion of the mold surface. The film is a leading edge protection material for a wind turbine blade. The leading edge protection material of this embodiment can also be said to be a gel coating. That is, the film functions as both a leading edge protection material and a gel coating.

[0133] A coating other than the coating may be formed on a portion of the mold surface other than the portion where the coating is formed. In one embodiment, the coating is a leading edge protection material, and the other coating is a gel coating used in a general wind turbine blade.

[0134] After the resin composition is applied to a portion of the mold surface to form a film, a second resin composition different from the above resin composition may be applied to form a second film in a manner covering the film and at least a portion of the mold surface. Examples of the second resin composition include gel coating agents commonly used in wind turbine blades.

[0135] 〈Configuration process〉

[0136] In the placement step, a fiber-containing substrate impregnated with a matrix resin is placed on the film to form a stacked body. Examples of the fiber-containing substrate impregnated with a matrix resin include prepregs containing glass fibers or carbon fibers.

[0137] The disposing step may include: impregnating the fiber base material with the matrix resin on the film to form a fiber-containing base material. The impregnation may be performed using, for example, a hand lay-up method or a vacuum-assisted impregnation construction method.

[0138] As a fiber substrate, for example, a substrate comprising fibers such as glass fiber, carbon fiber, polyester fiber, aramid fiber, vinylon fiber, cellulose nanofiber, etc. can be cited. As a fiber substrate, for example, short fibers, long fibers, twisted yarns, chopped fibers, chopped strands, continuous strands, rovings, nonwoven fabrics, rovings, woven fabrics, braids, materials having the shape of a three-dimensional woven fabric or a three-dimensional braid can be used. As a nonwoven fabric, for example, spunbonded nonwoven fabrics and meltblown nonwoven fabrics can be cited. As a woven fabric, for example, plain weave, satin weave, and twill can be cited.

[0139] As the matrix resin, a resin generally used for FRP molding can be used. As the matrix resin, for example, a thermosetting epoxy resin can be mentioned.

[0140] Reference Figure 2 (c) and (d) illustrate a method for forming a fiber-containing substrate by impregnating a fiber substrate with a matrix resin on a film using a vacuum-assisted impregnation construction method. Figure 2 As shown in (c) of FIG. 1 , the fiber substrate 142 is arranged so as to cover the film 12 and the mold surface 22. Figure 2 As shown in (d), the sheet 26 is arranged on the fiber substrate 142 so that the space between the sheet 26 and the mold surface 22 is airtight. An exhaust port 28 is provided at the end of the sheet 26. The exhaust port 28 is connected to a vacuum pump, and by operating the vacuum pump, the space between the sheet 26 and the mold surface 22 can be placed under reduced pressure. A matrix resin supply device 30 containing a matrix resin 144 is provided at the other end of the sheet. By opening the valve 32 and operating the vacuum pump to reduce the pressure of the space between the sheet 26 and the mold surface 22, the matrix resin 144 is impregnated in the fiber substrate 142, and the fiber-containing substrate 14 is formed on the film 12. The fiber-containing substrate 14 and the film 12 together form a stacked body 16.

[0141] 〈Heating process〉

[0142] In the heating step, the stack is heated to form a molded product in which the film is bonded to the fiber-containing substrate. The film preferably comprises a cured product of the resin composition, i.e., a cured film. Since the cured film is more firmly bonded to the fiber-containing substrate, a molded product with better corrosion resistance can be obtained.

[0143] like Figure 2 As shown in (e) of FIG. 1 , the heater 24 is operated to heat the stack 16. Thus, the film 12 and the fiber-containing substrate 14 are bonded to form a Figure 1 A wind turbine blade 10 is shown.

[0144] The heating temperature may be, for example, 50° C. to 200° C. The heating time may be, for example, 30 minutes to 24 hours.

[0145] When the fiber-containing base material is a prepreg, for example, autoclave molding or press molding can be used.

[0146] In one embodiment, the film is arranged at least on the front end portion of the leading edge of the wind power generation blade. The front end portion of the leading edge refers to, for example, the portion of the leading edge extending from the end farthest from the rotation axis of the wind power generation blade by 1% to 50%, 5% to 40%, or 10% to 30% of the blade length of the wind power generation blade. This embodiment is suitable for large wind power generation blades that are prone to erosion due to the high-speed movement of the front end portion. The film may also be arranged on the entire surface including the front end portion of the leading edge, or may be arranged on the entire surface of the wind power generation blade.

[0147] The blade length of the wind power generation blade is preferably 10 m or more, more preferably 20 m or more, and further preferably 30 m or more. The blade length of the wind power generation blade can be, for example, 140 m or less, 100 m or less, or 80 m or less. Any combination of these lower limit values ​​and upper limit values ​​can be used. In one embodiment, the blade length of the wind power generation blade is 10 m to 140 m, 20 m to 100 m, or 30 m to 80 m.

[0148] By using the resin composition of the present disclosure, a leading edge protection material having excellent properties can be formed on a wind turbine blade.

[0149] Example

[0150] Examples, comparative examples, and reference examples related to the present invention are shown below, but the present invention is not limited to these.

[0151] [Viscosity at 25°C]

[0152] The viscosity of the resin composition was evaluated by the following procedure. The shear viscosity at 25°C and a rotation speed of 100 rpm was measured using a cone / plate viscometer (RE-215U, manufactured by Toki Sangyo Co., Ltd., rotor: 1°34'×R24) in accordance with JIS K 5600-2-3:2014 "General test methods for coatings - Part 2: Properties and stability of coatings - Section 3: Viscosity (cone / plate viscometer method)".

[0153] The physical properties of the molded article were evaluated by the following procedures.

[0154] [Corrosion resistance]

[0155] A high-pressure washer (SH-0807, manufactured by Super Industries, Ltd.) was used with a water pressure of 6.0 MPa, a water volume of 6 L / min, and a test piece-nozzle distance of 7 cm. After direct water flow was applied to a 50 mm × 60 mm × 2 mm (thickness) test piece at 23°C for 30 consecutive minutes, the presence or absence of damage to the test piece was visually confirmed. The time required until damage occurred was defined as corrosion resistance.

[0156] [Adhesion strength]

[0157] In accordance with JIS K 5600-5-7:2014 "General Test Methods for Coatings - Part 5: Mechanical Properties of Coating Films - Section 7: Adhesion (Pull-off Method)", a film with a thickness of 0.5 mm was formed on a standard glass epoxy plate (60 mm × 150 mm × 2 mm (thickness), manufactured by Nippon Test Paner Co., Ltd.), and a dolly (20 mm in diameter, made of aluminum) was fixed to the film using an adhesive (Metalloc (trademark), manufactured by Semidine Co., Ltd.), and then the bonding strength was measured using an adhesion tester (Poji Test AT-A, manufactured by COTEC Co., Ltd.). The adhesive strength is defined as an average value measured at N=3.

[0158] [Resistance to humidity and heat cycles]

[0159] The test piece (50 mm × 80 mm × 2 mm (thickness)) was placed in a constant temperature and humidity chamber (PL-2J, manufactured by Espec Corporation) and subjected to 100 cycles of repeated heat and humidity cycles at -40°C for 6 hours and at 60°C and 98% relative humidity for 6 hours. The presence of powdering, bubbling, and cracks in the appearance was visually confirmed.

[0160] A: No powdering, bubbling or cracks

[0161] B: No cracks, no powdering, and no blistering

[0162] C: No cracks

[0163] D: Cracks have occurred

[0164] Table 1 shows the materials used for the synthesis of the urethane (meth)acrylate resin and the epoxy (meth)acrylate resin.

[0165]

[0166] The materials used to prepare the resin composition are shown below.

[0167] Dry silica レオロシールPM-20L (manufactured by Tokuta Co., Ltd.)

[0168] Titanium oxide PFC-105 (manufactured by Ishihara Sangyo Co., Ltd.)

[0169] Glass powder CF0033 (manufactured by タカラスタンダード Co., Ltd.)

[0170] Glass sheet (trademark) RCF-160N (manufactured by Nippon Sheet Glass Co., Ltd.)

[0171] DISPERBYK-2152 (manufactured by BYK Biotech Co., Ltd.)

[0172] 8% cobalt 2-ethylhexanoate (Toei Chemical Co., Ltd. 8%, manufactured by Toei Chemical Co., Ltd.)

[0173] Curing agent 328E (tert-butyl peroxybenzoate, cumene hydroperoxide mixture, manufactured by Chemical Nureion Co., Ltd.)

[0174] Parkmil (trademark) H-80 (cumene hydroperoxide, manufactured by NOF Corporation)

[0175] The urethane (meth)acrylate resin and the epoxy (meth)acrylate resin were synthesized by the following steps.

[0176] [Synthesis Example 1: Urethane (meth)acrylate resin UAc-1]

[0177] In a flask equipped with a stirrer, a reflux cooling tube, a thermometer, and a gas introduction tube, 142 g of 4,4'-methylenebiscyclohexyl diisocyanate (Desmogel W, manufactured by Sumika Cobstrowell Co., Ltd.), 411 g of polycarbonate diol (ETERNACOLL PH-100, manufactured by UBE Co., Ltd.), and 0.4 g of dibutyltin dilaurate were added, and the mixture was reacted at 80°C for 4 hours while heating and stirring. Then, 46 g of 2-hydroxyethyl methacrylate was added, and the mixture was reacted at 80°C for 4 hours while blowing dry air and heating and stirring, thereby obtaining a urethane (meth)acrylate resin UAc-1.

[0178] [Synthesis Examples 2 to 7: Urethane (meth)acrylate resins UAc-2 to UAc-7]

[0179] Except that the raw materials and their blending amounts were as described in Table 2, the same procedure as in Synthesis Example 1 was carried out to obtain urethane (meth)acrylate resins UAc-2 to UAc-7.

[0180] [Synthesis Example 8: Epoxy (meth)acrylate resin EAc-1]

[0181] In a flask equipped with a stirrer, a reflux cooling tube, a thermometer, and a gas inlet tube, 683 g of bisphenol A type epoxy resin (Epomic R140, manufactured by Mitsui Chemicals Fiine Co., Ltd.), 313 g of methacrylic acid, 3.0 g of triethylamine, and 0.6 g of hydroquinone were added, and the mixture was reacted at 120° C. while blowing air. The mixture was cooled when the acid value became less than 5 mgKOH / g, thereby obtaining epoxy (meth)acrylate resin EAc-1.

[0182] [Synthesis Example 9: Epoxy (meth)acrylate resin EAc-2]

[0183] Except having used the raw materials and their blending amounts as described in Table 2, the same procedure as in Synthesis Example 8 was carried out to obtain epoxy (meth)acrylate resin EAc-2.

[0184]

[0185] The resin composition was prepared by the following steps.

[0186] [Example 1]

[0187] 40 g of the urethane (meth) acrylate resin UAc-1 obtained in the above Synthesis Example 1, 60 g of vinyl toluene, 0.5 g of 8% cobalt 2-ethylhexanoate, and 1.5 g of curing agent 328E were added, and stirred at 2000 rpm for 1 minute using an autorotating and orbiting mixer to obtain the resin composition of Example 1.

[0188] The resin composition was poured into a silicone mold with a depth of 2 mm, and placed at 23° C. for 3 hours as pre-curing, and placed at 70° C. for 6 hours as post-curing to obtain a molded product of the resin composition. The pre-curing corresponds to the process of applying the resin composition to the mold surface to form a film, and the post-curing corresponds to the process of heating the stacked body of the film and the fiber-containing substrate. The evaluation results of the resin composition and the molded product are shown in Table 3.

[0189] [Example 2 to Example 15, Comparative Example 1 to Comparative Example 4]

[0190] A resin composition was obtained by the same procedure as in Example 1 except that the raw materials and their blending amounts were as shown in Table 3. A molded article was obtained from the obtained resin composition by the same procedure as in Example 1. Table 3 shows the evaluation results of the resin composition and the molded article.

[0191] [Reference Example 1 to Reference Example 3]

[0192] Using the resin composition of Example 1, a molded article was obtained by performing only pre-curing without performing post-curing under the conditions described in Table 3. Table 3 shows the evaluation results of the molded article.

[0193] [Example 16]

[0194] A molded article was obtained by the same procedure as in Example 1 except that the resin composition of Example 1 was poured into a silicone mold having a depth of 0.1 mm. Table 3 shows the evaluation results of the molded article.

[0195]

[0196]

[0197]

[0198] Industrial Availability

[0199] The resin composition disclosed herein is suitable for manufacturing a leading edge protection material for a wind power generation blade.

[0200] Explanation of symbols

[0201] 10 Wind turbine blades

[0202] 12 membrane

[0203] 14. Fiber-containing substrate

[0204] 142 Fiber substrate

[0205] 144 Base resin

[0206] 16 stacked

[0207] 20 molds

[0208] 22Mold surface

[0209] 24 Heater

[0210] 26 pieces

[0211] 28 Exhaust port

[0212] 30 Matrix resin supply device

[0213] 32 valves.

Claims

1. Use of a resin composition comprising a urethane resin having a urethane structure and a carbonate structure in the same molecule as a gel coating and leading edge protective agent for a wind turbine blade. 2 . The use according to claim 1 , wherein the urethane resin is a urethane (meth)acrylate resin. 3 . The use according to claim 1 , wherein the resin composition further comprises an epoxy (meth)acrylate resin. 4 . The use according to claim 1 , wherein the resin composition comprises 10% by mass to 90% by mass of the urethane resin.

5. The use according to claim 1 or 2, wherein the urethane resin is a reaction product of a composition comprising a polycarbonate polyol and a polyisocyanate, and a molar ratio of a hydroxyl group of the polycarbonate polyol to an isocyanate group of the polyisocyanate, i.e., OH [mol] / NCO [mol], is 0.5 to 0.

9. 6 . The use according to claim 5 , wherein the number average molecular weight of the polycarbonate polyol is 500 to 10,000.

7. The use according to claim 5, wherein the polyisocyanate comprises an alicyclic polyisocyanate.

8. The use according to claim 1 or 2, wherein the urethane resin has a number average molecular weight of 500 to 30,000.

9. The use according to claim 1 or 2, wherein the wind power generation blade has a blade length of 10 m or more.